Quantitative Estimation of Quercetin by HPTLC And Exploring Anti-Inflammatory and Anti-Cancer Potential of Althaea Officinalis Linn. - Saini, Annu; Bhan, Meenu (Journal of Neonatal Surgery, 2025)
The objective of the study aims to explore the medicinal importance of Althaea officinalis Linn as anti-inflammatory and anti-cancer agent. Molecular docking, Preliminary Phytochemical screening, quantification of quercetin by High Performance Thin Layer Chromatography, in-vitro anti-inflammatory and anti-cancer activities of Althaea officinalis root extracts were done. Docking of ligands with different target proteins was performed by schrodinger software. Aqueous extract was prepared by different extraction techniques like maceration, UAE and MAE. High Performance Thin Layer Chromatography (HPTLC) was used for the quantification of quercetin. In-vitro anti-inflammatory screening was performed by Hyaluronidase inhibition assay and Human Red Blood Cell stabilization assay. The anti-cancer activity of extracts was evaluated by MTT assay using A431 cell line. MAPK, Braf, P53, PD1 and COX-2 anti-inflammatory and anti-cancer target proteins were used for molecular docking of quercetin and it showed best docking score -4.00564 against PD1. The minimum 26.732+0.5 %w/w and maximum 52.76+.03% w/w extraction yield was found in aqueous extract. Quercetin was quantitatively determined by HPTLC and found maximum quantity in MAE extract 2.513µg/ml. In-vitro anti-inflammatory screening was performed by Hyaluronidase inhibition assay and Human Red Blood Cell stabilization assay. The maximum percentage of inhibition (96.77+1.22%) in Hyaluronidase assay and (98.39+2.1%) in HRBC assay was observed in MAE extract at higher concentration. The anti-cancer activity of extracts was evaluated by MTT assay using A431 cell line. The IC50 value of UAE extract was found to be 88.12µg/ml and IC50 of maceration, MAE extracts were 92.46µg/ml and 98.94µg/ml.